Effect of Pickering stabilization on radical entry in emulsion polymerization. Issue 7 (26th March 2018) - Brunier, Barthélémy; Sheibat‐Othman, Nida; Chevalier, Yves; Bourgeat‐Lami, Élodie
Abstract : The production of latexes stabilized by solid particles, so‐called Pickering stabilizers, has attracted considerable attention due to its benefits, including the enhanced mechanical properties of the polymer films. Clays for instance were found to enhance particle stabilization in emulsion polymerization, in a comparable way to conventional surfactants. Their concentration thus determines the polymer particles size and number, and consequently the reaction rate. In this work, we investigate the impact of the presence of such rigid and big platelets at the polymer particle's surface on radical exchange between the aqueous phase and the polymer particles. It was found for the system underhand that the average number of radicals per particle ( n ¯ ) was independent of the stabilizer layer. Therefore, a radical capture model independent of the clay concentration could be used to simulate reactions involving different clay concentrations and predict the evolution of the monomer conversion, particle size, and n ¯ . © 2018 American Institute of Chemical Engineers AIChE J, 64: 2612–2624, 2018